The Burden of Injury in terms of Economic Loss and Disability Days: A Community Based Study from Eastern Nepal - Ghimire, A; Nagesh, S; Jha, N; Niraula, S R; Devkota, S (Kathmandu University Medical Journal, 2012)
Background Injuries are already a substantial public Health problem all over the world and are expected to increase in the 211st Century. They are major causes of deaths and disability in the population and also involve high societal costs. Objectives This study was designed to assess the economic loss due to the injury and the disability days due to different types of injuries. Methods A systematic random sampling technique was used to select 1388 households from 19 wards. A detailed questionnaire was used to collect information related to injuries to the persons suffered from injuries including treatment obtained, cost of treatment (direct/indirect cost) and length of disability. Results Among the minor injured persons, majority (93.2%) did not spend any indirect cost. 36.7% of the major inured persons spent Nepalese rupees 10,001 to NRs 100,000 as direct treatment costs. But 50% spent less than 5000 NRs as indirect cost for major injury treatment. Maximum number (67.4%) of major injured persons had disability days of 31 to 90 days. Conclusion The high incidence of injuries, especially road traffic injuries, adds a huge economic burden to nation.DOI: http://dx.doi.org/10.3126/kumj.v9i2.6283Kathmandu Univ Med J 2011;9(2):27-30